Measuring Critical Thinking in Physics: A Rasch Analysis of Instrument Quality and Gender Equivalence - Maria Goreti Halim; Duden Saepuzaman; Lina Aviyanti; Judhistira Aria Utama; Abu Nawas (FKIP Universitas Lampung, 2026)
This study seeks to evaluate the quality of a Critical Thinking Skills (CTS) instrument for high school students on dynamic fluids, focusing on reliability, item validity, and respondent ability assessment using the Rasch model. This research utilized a quantitative technique with a descriptive design. The research sample comprised 200 11th-grade science students from several high schools in Manggarai Regency, East Nusa Tenggara, Indonesia, of whom 140 were female, and 60 were male. Data were analyzed with the Rasch modeling approach with the assistance of WINSTEPS software version 3.73. The findings indicated that the instrument exhibited generally acceptable psychometric properties, with a Cronbach’s Alpha of 0.89 and a reliability of 0.93, indicating strong internal consistency and measurement stability. However, Rasch model analysis revealed that approximately 10% of the items did not fit the model expectations (misfit), around 15% indicated potential gender bias based on Differential Item Functioning (DIF) analysis, and 20,5% of respondents showed misfit response patterns. These results suggest that, while the overall reliability indices were high, certain items and response patterns require further refinement to achieve optimal measurement precision and fairness. The person reliability score of 0.83 indicated that the instrument reliably and accurately differentiated between varied levels of responder competence in assessing critical thinking abilities. In conclusion, this CTS instrument demonstrates overall acceptable measurement quality within the Rasch framework, although several psychometric limitations remain evident. These findings position the instrument as a preliminary yet functional assessment tool for measuring students’ critical thinking skills in dynamic fluid topics, while highlighting the importance of continued empirical validation. Future studies are encouraged to expand the range of item difficulty, re-examine items exhibiting misfit and gender-related DIF, and involve more diverse samples to enhance measurement precision, fairness, and generalizability. Keywords: critical thinking skills, Rasch model, dynamic fluids.